2011
DOI: 10.1093/eurjhf/hfq183
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of sleep disordered breathing and its treatment in heart failure: an observational study

Abstract: AimsSleep disordered breathing (SDB) may contribute to disease progression in patients with chronic heart failure (CHF). The objective of this observational study was to evaluate whether SDB is a risk factor for mortality in CHF patients and whether this risk can be attenuated by treatment with positive airway pressure (PAP). ) and (ii) evaluated the impact of PAP treatment on mortality in those with severe SDB. After accounting for significant confounding factors (age, NYHA class, cause of CHF, diabetes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 36 publications
1
117
1
8
Order By: Relevance
“…Thus the prevalence of CSA and OSA in the AMI patients of our study is comparable with that reported in samples of patients with chronic HF and with a similar degree of cardiac impairment [1,3]. In such samples of chronic HF, CSA, as well as OSA, is associated with impaired prognosis [8,9].…”
Section: Sleep-related Disorders S Buchner Et Alsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus the prevalence of CSA and OSA in the AMI patients of our study is comparable with that reported in samples of patients with chronic HF and with a similar degree of cardiac impairment [1,3]. In such samples of chronic HF, CSA, as well as OSA, is associated with impaired prognosis [8,9].…”
Section: Sleep-related Disorders S Buchner Et Alsupporting
confidence: 86%
“…Polysomnography PSG was performed in all subjects using standard polysomnographic techniques (Alice System; Respironics, Pittsburgh, PA, USA) [8]. Respiratory efforts were measured with the use of respiratory inductance plethysmography and airflow by nasal pressure.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of multiple studies using ASV as a contrast group (O 2 , CPAP, or continued medical therapy), will show that ASV improves AHI and LVEF signifi cantly [63]. Two observational long-term studies [8,10] have demonstrated improved survival in those who used the ASV device compared to those who refused. Currently, 2 large prospective trials are ongoing -SERVE-HF and ADVENT-HF.…”
Section: Central Sleep Apneamentioning
confidence: 99%
“…It leads to further deterioration of cardiac function and worsens prognosis [3][4][5][6]. SDB may be a potential therapeutic target as its effective treatment improves quality of life, exercise tolerance and, possibly, long term prognosis [5][6][7][8][9][10]. However, the importance of SDB remains unrecognized and the disorder itself is diagnosed rarely and remains untreated [5].…”
Section: Introductionmentioning
confidence: 99%